Investigation of Salmonella prevalence, quantification with a method comparison, and serotyping in market hog lymphoid tissues - Fashenpour, Erin Elizabeth (Kansas State University, 2023)
The United States Department of Agriculture Food Safety and Inspection Service (USDA FSIS) will soon release performance standards for Salmonella in pork that will affect change in the meat industry. Although somewhat limited in comparison to other protein sources, food safety professionals need to address foodborne illness caused by pork-related products. Lymph nodes (LNs) have been researched frequently in recent years in the meat industry to investigate Salmonella harborage and presence in ground product. The first study evaluated the prevalence and concentration of Salmonella in market hog LNs and tonsils. Regional and seasonal variability were also explored. An enumeration method comparison was performed between the 3M™ EB Petrifilm™ + XLD replica plate method and BAX®-System-SalQuant®. Samples were collected from six participating pork processing facilities, located in three pre-determined regions (east, central, and west). Samples were collected during three seasons (winter, spring, and fall) from each plant, where 30-35 carcasses were selected at random on the harvest floor. From each carcass, seven sample types were collected, including mesenteric, subiliac, superficial inguinal, prescapular, axillary, tracheobronchial LNs, and tonsils. Samples were evaluated using BAX Salmonella Real-time PCR Assay for a Salmonella detection step. Positive samples were then evaluated for Salmonella quantification using BAX®-System-SalQuant® methods. Of the 4,132 samples collected, 14% were positive for Salmonella. A season-by-region interaction was observed for Salmonella prevalence in axillary and tracheobronchial LNs, and tonsils (P<0.05). Of these three sample types, tonsils had the highest prevalence observed in the eastern region in the spring season (74.2%). In general, Salmonella prevalence appears to be greatest in the eastern region during spring, though this varies with sample type. Tonsils and mesenteric LNs had the highest overall prevalence at 35% and 34%, respectively, however a season-by-region interaction was not detected for mesenteric LN prevalence. Salmonella prevalence by carcass was 62% out of the 601 total carcasses; a season-by-region interaction was observed (P=0.001). The highest carcass prevalence occurred during the spring in the eastern region (90.9%), and the lowest prevalence occurred during the spring in the central region (26.0%). Only tonsils and mesenteric LNs were statistically evaluated for Salmonella concentration. Median Salmonella concentrations fell below the limit of quantification for mesenteric LNs, while median concentration for tonsils was 2.18 log₁₀ CFU/sample using BAX®-System-SalQuant®. The method comparison results showed that the 3M™ EB Petrifilm™ + XLD replica plate method and BAX®-System-SalQuant® can be used for quantification, however there are benefits and pitfalls to both. Following statistical analysis, a kappa coefficient value of 0.384 was observed between 3M™ EB Petrifilm™ + XLD replica plate method and BAX®-System-SalQuant®, indicating a fair agreement between the Salmonella quantification methods. A t-test was also performed on the 83 samples that were quantified by both methodologies, where no significant difference was observed in the mean log CFU/sample (P>0.05). Salmonella was isolated from market hog LNs and tonsils, and isolates were subjected to serotyping. Serotype is an important variable to consider when evaluating the risk of contamination from these sample types. Not all serotypes are pathogenic to humans, however some are known to be more virulent or even deadly. The most isolated serotypes included monophasic S. Typhimurium, followed by S. Agona and S. Schwarzengrund, all of which can be pathogenic to humans. While most isolates were recovered from mesenteric LNs and tonsils, pathogenic Salmonella was recovered from peripheral LNs, which pose a greater risk of contamination in consumer products. These data will allow for a risk assessment of Salmonella prevalence, concentration, and serotypes to improve understanding of how contaminated market hog lymph nodes affect risk to human health.
Keywords: Salmonella; Pork; Lymph nodes; Tonsils